Stem Cell Therapy for Ischemic Heart Disease: Clinical Use - PURWOWIYOTO, Sidhi Laksono (Sanus Medical Journal, 2020)
Ischemic heart disease is still becoming a cause of morbidity and mortality in the world. Regenerative cellular or stem cell therapy is a new and emerging as an alternative option for this disease. There are several stem cell types that used in ischemic heart disease, most used stem cell for this treatment are bone marrow-derived stem cell and mesenchymal stem cell. The mechanism of action for stem cell therapy is depends on transdifferentiation and paracrine effect. It effects the release of cytokines, chemokines and growth factors that inhibits apoptosis and fibrosis, enhance contractility and activate regenerative mechanism. Factors associated with the efficacy of stem cell therapy are delivery route to target myocardium, number of stem cell infusion, injection timing, physical condition of patient and stem cell microenvironment.